The Impact of Hybrid Work on the Quality of Interpersonal Relations in the HR Department of the Enterprise – A Case Study - Mirosław Wójcik; Magdalena Poroszewska (European Management Studies)
Purpose: The purpose of this article is to answer the question of whether the implementation of hybrid work organization results in a quality change of interpersonal relations in an HR Department. Methodology: To achieve the stated goal, the authors decided to conduct a case study in a large, dispersed organization. Empirical data were obtained through an online research questionnaire, an individual in-depth interview, and the IT systems of the organization under study. Findings: As a result of the study, it was shown that in the examined HR Department, the implementation of hybrid work organization did not change the quality of employee relations. The results contradict some existing sources, making us assume that the impact of hybrid work on employee relations is not unequivocal. Therefore, there are possible situations where its negative or positive effect does not exist. This opens a wide range of possibilities for applying hybrid work methods without negatively impacting the organization. Originality/value: The literature is scarce when it comes to analyzing the impact of hybrid work organization on employee relations. Most of the available material is based on reports from consulting companies and its scientific value is impossible to examine. Even less literature addresses the issue of interpersonal relations in the post-pandemic era.